2022
DOI: 10.1021/acs.est.2c02371
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Methane Production to Boost High-Purity Hydrogen Production in Microbial Electrolysis Cells

Abstract: Hydrogen gas (H2) is an attractive fuel carrier due to its high specific enthalpy; moreover, it is a clean source of energy because in the combustion reaction with oxygen (O2) it produces water as the only byproduct. The microbial electrolysis cell (MEC) is a promising technology for producing H2 from simple or complex organics present in wastewater and solid wastes. Methanogens and non-archaeal methane (CH4)-producing microorganisms (NAMPMs) often grow in the MECs and lead to rapid conversion of produced H2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 194 publications
0
8
0
Order By: Relevance
“…50,51 Theoretically, the increased hydrogen production should be related to decreased methane generation. 50,52 However, we observed enhanced hydrogen evolution in conjunction with a stable methane yield (Figure S3d). It was obvious that the higher cathodic Coulombic efficiency should be ascribed to augmented hydrogen production, which could be caused by a lower methane sink at the cathode.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…50,51 Theoretically, the increased hydrogen production should be related to decreased methane generation. 50,52 However, we observed enhanced hydrogen evolution in conjunction with a stable methane yield (Figure S3d). It was obvious that the higher cathodic Coulombic efficiency should be ascribed to augmented hydrogen production, which could be caused by a lower methane sink at the cathode.…”
Section: Resultsmentioning
confidence: 77%
“…Although hydrogen evolution could be independent of microbial processes, the biocathode has been shown to produce hydrogen in MECs . Substantially, the main contributor of methane production was confirmed as methanogens in the cathodic biofilm via the hydrogenotrophic pathway. , Thereby, biomass retention on the electrode was verified as an important factor in determining its performance in methane production, as well as for hydrogen accumulation through the provision of an electron donor. , Theoretically, the increased hydrogen production should be related to decreased methane generation. , However, we observed enhanced hydrogen evolution in conjunction with a stable methane yield (Figure S3d). It was obvious that the higher cathodic Coulombic efficiency should be ascribed to augmented hydrogen production, which could be caused by a lower methane sink at the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1,2 ] Hydrogen (H 2 ) is considered a sustainable, clean, and environmentally friendly energy source with great potential as a future energy carrier due to its high energy density (142 MJ kg −1 ) and ability to be manufactured in a variety of ways. [ 3,4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Hydrogen (H 2 ) is considered a sustainable, clean, and environmentally friendly energy source with great potential as a future energy carrier due to its high energy density (142 MJ kg −1 ) and ability to be manufactured in a variety of ways. [3,4] Photocatalytic water splitting has been recognized as the most attractive way to produce H 2 . [5][6][7] However, extremely high recombination of photogenerated carriers limits the efficiency of most photocatalysts, which usually needs cocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial electrolysis cells (MECs) has become a prospective and sustainable technology for high-efficiency chemical production (e.g., H 2 O 2 and H 2 ) from wastewaters (He et al, 2022;Li et al, 2016;Zhang and Angelidaki, 2014). Recently, our group found that dissolved Fe(II) can be regenerated from ferric sludge at near-neutral pH, in the biocathode of MEC (Guan Wang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%